2008
DOI: 10.1016/j.socscimed.2008.03.034
|View full text |Cite
|
Sign up to set email alerts
|

The Cedar Project: Historical trauma, sexual abuse and HIV risk among young Aboriginal people who use injection and non-injection drugs in two Canadian cities

Abstract: Recent Indigenist scholarship has situated high rates of traumatic life experiences, including sexual abuse, among Indigenous peoples of North America within the larger context of their status as colonized peoples. Sexual abuse has been linked to many negative health outcomes including mental, sexual and drug-related vulnerabilities. There is a paucity of research in Canada addressing the relationship between antecedent sexual abuse and negative health outcomes among Aboriginal people including elevated risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…Given that incarceration has been associated with both HIV risk behaviours [15] and HIV incidence [16] in Vancouver, interventions to reduce street youths' exposure to correctional environments and the HIV-related harms associated with them are in urgent need of evaluation. Of further concern is that over half of HIV-infected Aboriginal participants reported experiencing sexual abuse, a finding which supports a recent study showing strong associations between sexual abuse and HIV risk behaviours among this population [17]. These results suggest that programs which aim to support HIV positive Aboriginal young people should recognize and address the lasting effects of historical trauma and cultural assimilation stemming from the Canadian residential school system on current levels of sexual abuse, substance use, and other HIV-related vulnerabilities.…”
Section: Discussionsupporting
confidence: 71%
“…Given that incarceration has been associated with both HIV risk behaviours [15] and HIV incidence [16] in Vancouver, interventions to reduce street youths' exposure to correctional environments and the HIV-related harms associated with them are in urgent need of evaluation. Of further concern is that over half of HIV-infected Aboriginal participants reported experiencing sexual abuse, a finding which supports a recent study showing strong associations between sexual abuse and HIV risk behaviours among this population [17]. These results suggest that programs which aim to support HIV positive Aboriginal young people should recognize and address the lasting effects of historical trauma and cultural assimilation stemming from the Canadian residential school system on current levels of sexual abuse, substance use, and other HIV-related vulnerabilities.…”
Section: Discussionsupporting
confidence: 71%
“…However, having had a parent attend a residential school was found to be associated with sexual abuse in a sample of 14-30 year old Aboriginals who use drugs in a bivariate analysis (Cedar Project Partnership et al, 2008). On the other hand, no differences were found in terms of levels of happiness, quality of life, and quality of relationships with family members between Aboriginals who had and had not gone to residential schools (Barton et al, 2005).…”
Section: Correlates Of Suicidality 11mentioning
confidence: 92%
“…Particularly noteworthy was abuse/fear of abuse, which was strongly related to SI, SA, and any suicidality in bivariate analyses and remained a significant correlate of suicidality in the most stringent multivariate model. Victims of abuse have been shown to be at risk for a range of negative outcomes in indigenous samples, including several mental disorders and engagement in problem behaviour (Cedar Project Partnership et al, 2008;Libby et al, 2005;Robin, Chester, Rasmussen, Jaranson, & Goldman, 1997b). It is possible that in communities where most people know one another, youth who are abused are at risk of not getting help because they have no one whom they trust to disclose their experience.…”
Section: Methodsmentioning
confidence: 99%
“…One study looked at the experiences of 543 Aboriginal people between 14-30 years of age who use drugs and reside in Prince George or Vancouver (Cedar et al 2008). Fifty percent had at least one parent who had attended residential school and 73°/o had been taken from their biological parents into care (Cedar et al 2008(Cedar et al , p. 2189.…”
Section: Facilitators and Barr Iers To Medical Evaluationmentioning
confidence: 99%
“…One study looked at the experiences of 543 Aboriginal people between 14-30 years of age who use drugs and reside in Prince George or Vancouver (Cedar et al 2008). Fifty percent had at least one parent who had attended residential school and 73°/o had been taken from their biological parents into care (Cedar et al 2008(Cedar et al , p. 2189. They found that 48°/o reported a history of sexual abuse and that this was predictive of vulnerability to adverse health outcomes including HIV infection , involvement in survival sex, history of self-harm , suicidal ideation , suicide attempts , and overdose (Cedar et al) .…”
Section: Facilitators and Barr Iers To Medical Evaluationmentioning
confidence: 99%